LAR and PTPσ receptors are negative regulators of oligodendrogenesis and oligodendrocyte integrity in spinal cord injury. Issue 1 (5th November 2018) - Dyck, Scott; Kataria, Hardeep; Akbari‐Kelachayeh, Khashayar; Silver, Jerry; Karimi‐Abdolrezaee, Soheila
Abstract: Following spinal cord injury (SCI), the population of mature oligodendrocytes undergoes substantial cell death; promoting their preservation and replacement is a viable strategy for preserving axonal integrity and white matter repair in the injured spinal cord. Dramatic upregulation of matrix chondroitin sulfate proteoglycans (CSPGs) is shown to pose an obstacle to endogenous repair processes, and targeting CSPGs improves functional recovery after SCI. However, the cellular and molecular mechanisms underlying the inhibitory effects of CSPGs remain largely undefined. Modulation of CSPGs specific signaling receptors, leukocyte common antigen‐related (LAR), and protein tyrosine phosphatase‐sigma (PTPσ) allows us to uncover the role and mechanisms of CSPGs in regulating oligodendrocytes in SCI. Here, utilizing specific functionally blocking peptides in a clinically relevant model of contusive/compressive SCI in the rat, we demonstrate that inhibition of PTPσ and LAR receptors promotes oligodendrogenesis by endogenous precursor cells, attenuates caspase 3‐mediated cell death in mature oligodendrocytes, and preserves myelin. In parallel in vitro systems, we have unraveled that CSPGs directly induce apoptosis in populations of neural precursor cells and oligodendrocyte progenitor cells and limit their ability for oligodendrocyte differentiation, maturation, and myelination. These negative effects of CSPGs are mediated through the activation of both LAR and PTPσ receptors and the downstream Rho/ROCK pathway. Thus, we have identified a novel inhibitory role for PTPσ and LAR in regulating oligodendrocyte differentiation and apoptosis in the injured adult spinal cord and a new feasible therapeutic strategy for optimizing endogenous cell replacement following SCI. Main Points: We show for the first time that LAR and PTPα play critical roles in regulating oligodendrocytes after spinal cord injury, and their inhibition provides new target to augment endogenous oligodendrocyte replacement and integrity in the injured spinal cord.